2011
DOI: 10.1590/s1806-83242011005000006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photodynamic therapy on clinical isolates of Staphylococcus spp

Abstract: Staphylococcus spp. are opportunistic microorganisms known for their capacity to develop resistance against antimicrobial agents. The objective of this study was to evaluate the effect of photodynamic therapy (PDT) on 20 Staphylococcus strains isolated from the human oral cavity, including S. aureus, S. schleiferi, S. epidermidis, S. capitis, S. haemolyticus, and S. lentus. A suspension of each Staphylococcus strain (10 6 cells/ mL) was submitted to PDT using methylene blue and a low power laser. The isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 22 publications
6
17
0
3
Order By: Relevance
“…The findings of the in vitro resistance test for PDT corroborate other studies in the literature that show that PDT is capable of destroying resistant microorganisms even after prolonged use of antibiotics [21,22]. However, it is well established that susceptibility of microorganisms to PDT is dependent on several factors such as concentration of photosensitizer, pre-irradiation time, kind of microorganism, and irradiation time.…”
Section: Resultssupporting
confidence: 84%
“…The findings of the in vitro resistance test for PDT corroborate other studies in the literature that show that PDT is capable of destroying resistant microorganisms even after prolonged use of antibiotics [21,22]. However, it is well established that susceptibility of microorganisms to PDT is dependent on several factors such as concentration of photosensitizer, pre-irradiation time, kind of microorganism, and irradiation time.…”
Section: Resultssupporting
confidence: 84%
“…We obtained the same results for the eradication of S. aureus with a light dose of 12 J/cm 2 , whether the irradiation time was 10 or 60 min (data not shown). To inactivate clinical isolates of Staphylococcus species, Miyabe et al used 3 mM MB and a light fluence of 26.3 J/cm 2 (gallium-aluminum-arsenide laser, 660 nm) to obtain a mean reduction of 6.29 log 10  cfu/mL [56]. In S. mutans, Rolim et al did not observe photodynamic activity when MB was used at a concentration of 163.5  μ M at 24 J/cm 2 (LED, 640 nm), but a significant reduction (3 log 10  cfu/mL) was observed when the same concentration of TBO and an equal light dose were used [57].…”
Section: Antimicrobial Photodynamic Therapymentioning
confidence: 99%
“…In fact, it has been shown to significantly eradicate Staphylococcus sp [14, 23, 24], Pseudomonas sp 6 , or Candida sp [25]. Many studies have also shown the efficacy of PDT using in vivo models.…”
Section: Discussionmentioning
confidence: 99%